Assessment of the personnel-efficacy of Moroccan teachers and future teachers in the practice of gender-responsive pedagogy: case study of the Casablanca-Settat region - Aafaf, Essedaoui; Sabah, Belaaouja; Marya, Bouanis; Aziz, Boukhair; Mohamed, El Houch; Smail, Belaaouja (Frontiers in Education, 2025)
Gender equality in education is crucial for sustainable development and the realization of fundamental human rights. Gender-responsive pedagogy seeks to promote equal opportunities for all students, regardless of gender, by fostering an inclusive and respectful learning environment. This study, conducted as part of the HEP-Morocco project in collaboration with USAID and Arizona State University (ASU), examines the efficacy of Moroccan teachers and future teachers in implementing gender-responsive pedagogy. Specifically, it explores their awareness of the gender approach (Dimension 1), its application in teaching practices (Dimension 2), and the development of gender-related behaviors (Dimension 3). To assess these dimensions, a validated 31-item questionnaire was administered to 135 teachers and future teachers from the Casablanca-Settat regional academy. The findings indicate that awareness, implementation, and behavioral development related to gender-responsive pedagogy are at a clear level. Likewise, teachers' overall efficacy in applying the gender approach was found to be moderate (M = 92.28, SD = 28.03). The students-test and ANOVA analysis revealed no significant differences in these dimensions based on demographic factors such as gender, age, education level, teaching field, or employment status. However, statistically significant correlations were found between teachers' overall efficacy in practicing gender-responsive pedagogy and their knowledge, teaching methods, and developed behaviors, suggesting that these elements are closely interconnected.